(untitled) (Revista de Ciências Agroveterinárias, 2011)
The discontinuous electrophoresis system containing polyacrilamide and sodium dodecyl sulphate (SDS-PAGE) is used to separate polypeptide chains for subsequent protein profile analysis. However, the protein extraction and separation methods vary according to the vegetal species and little is reported about storage proteins in Handroanthus albus. Because of this, the objective of this work was to standardize a method of extracting and visualizing the protein profi le of H. albus seeds. Four methodologies were tested in the electrophoresis SDS-PAGE system, from a basic method, using a simple extraction buffer containing only Tris-HCl, to the most complex method with strong antioxidants, were used. Also, various modifications were made to the gel concentration in the sample buffer and the electrode buffer, in order to obtain neatness in the visualization of the protein profile. The method which allowed the best visualization of the protein profile was the one based on the use of 1 M of tris-HCl pH 8.8 in the extraction buffer and 20% glycerol; 1.73 mM of SDS; 1.54 mM tris-HCl-6.8; 0.036 mM bromophenol blue and 2% of β-mercaptoetanol in the sample buffer. The protein profile observed showed proteins with a molecular weight between 63 kDa and 25.6 kDa in separating gel 15% and the concentrator at 3%. Such methodology standardization serves as a basis for future works which have the objective of studying the protein profile associated with certain metabolic and or biochemical events in H. albus seed.